2018
DOI: 10.1094/mpmi-02-18-0049-r
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Mass Spectrometry of Endogenous Polypeptides and Secondary Metabolites from Galls Induced by Root-Knot Nematodes in Tomato Roots

Abstract: Nematodes are devastating pests that infect most cultivated plant species and cause considerable agricultural losses worldwide. The understanding of metabolic adjustments induced during plant-nematode interaction is crucial to generate resistant plants or to select more efficient molecules to fight against this pest. Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) has been used herein for in situ detection and mapping endogenous polypeptides and secondary metabolites from nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Moreover, all the ions shared the same localization at the level of the granular cells layer [91]. Only the species PI (40:6) was found in the granular cell layer but not in the gray matter, and the grey matter regions were differentiated by PI (38:4) and PC (32:0) as observed in other studies [88,89]. This differential phospholipids localization finds an explanation in the lipid processing, especially at the level of the hypothalamus [92].…”
Section: Animal Tissues As Exemplary For Molecular Imaging: Brain Testicles and Kidneysupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, all the ions shared the same localization at the level of the granular cells layer [91]. Only the species PI (40:6) was found in the granular cell layer but not in the gray matter, and the grey matter regions were differentiated by PI (38:4) and PC (32:0) as observed in other studies [88,89]. This differential phospholipids localization finds an explanation in the lipid processing, especially at the level of the hypothalamus [92].…”
Section: Animal Tissues As Exemplary For Molecular Imaging: Brain Testicles and Kidneysupporting
confidence: 82%
“…However, a few studies performed on Caenorhabditis elegans and Schistosoma mansoni showed promising results for lipid detection [83,86,87] (Supplementary Table S1). Moreover, a recent study investigated the effect of the parasitism of tomato roots by the nematode Meloidogyne incognita on polypeptides and secondary metabolites, but focused only on the plant side of the interaction [88] (Supplementary Table S1).…”
Section: Molecular Imaging In Insects Nematodes and Wormsmentioning
confidence: 99%
See 1 more Smart Citation
“…MALDI-MSI was used to analyze peptides, proteins, and secondary metabolites in uninfected tomato roots and nematode-induced galls. It was found that glycerophospholipids were present only in the nematode's feeding site, while other compositions only in the unaffected roots, suggesting that glycerophospholipids may be involved in the process of nematode infection and maintenance of root development [100]. MSI was also used to track the fate and transportation of several secondary plant metabolites in simulated ecosystems [101].…”
Section: Plant-environment Interactionsmentioning
confidence: 99%
“…The technique was used with success to monitor the presence of hesperidin and rutin in the infection site 32 . MSI was also applied to monitor other plant diseases 33 35 ; however, this technique has never been applied to understand the infection process of C Las in citrus. Herein, we applied for the first time MSI analyses combined with HPLC–MS/MS to investigate healthy and diseased leaves (both asymptomatic and symptomatic stages) in the search for HLB biomarkers.…”
Section: Introductionmentioning
confidence: 99%